MENINGKATKAN HASIL BELAJAR SISWA KELAS III PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM MATERI SHOLAT KEWAJIBANKU MELALUI METODE TALKING STIK DI SDN 3 GUMIRIH SINGOJURUH BANYUWANGI - Syamsudin, Moh. Anas; Utma, Ula Rohmatul (PGMI Department of Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia, 2023)
Prayer is the main obligation of Muslims, so it must be introduced to children as early as possible. In learning in elementary schools (SD) there are Islamic religious education subjects (PAI) with a focus on discussing material about prayer. The fact that happened that the scores of grade III students in the PAI lesson on my obligation prayer material at SDN Gumirih Singojuruh Banyuwangi were still relatively low, namely out of 16 students only 3 achieved completion scores. Talking stick is a fun method that can be used as an alternative solution to improve student learning outcomes on prayer material. This research was conducted at SDN Gumirih Singojuruh Banyuwangi with the research subjects being grade III students totaling 16. The research method used is classroom action research. Data collection techniques in this study are, interviews, observations, documentation, and tests. While there are 2 kinds of data analysis techniques used, namely individual and class average value analysis techniques. The results showed that there was an increase in the number of children who achieved completeness scores from pre-cycle data as many as 3 children, cycle 1 as many as 7 children and cycle 2 as many as 11 children with a comparison of class average scores in the pre-cycle of 58.25, cycle 1 69, 31, and cycle 2 80.25.